Specificity of anti-human CD95 (APO-1/Fas) antibodies - Schmitz, Ingo; Krammer, Peter H. (Biochemical and biophysical research communications, 2002)
The CD95 (APO-1/Fas) death receptor plays an important role in many physiological and pathophysiological systems. Thus, the CD95 system contributes to activation-induced cell death. Therefore, reliable antibodies recognizing human CD95 are of great interest. Detection of CD95 expression often relies on antibodies, e.g., suitable for Western blotting. To detect CD95, we compared the specificity of nine different anti-human CD95 antibodies recognizing different epitopes by using postnuclear supernatants of four different cell lines. Only two of the antibodies tested, both directed against intracellular epitopes of human CD95, detected endogenous human CD95 by Western blotting. Therefore, we conclude that results obtained with other anti-CD95 antibodies should be treated with caution.
Gesehen am 14.04.2021